On T-Curvature Tensor in LP-Sasakian Manifolds - Shah, Riddhi Jung (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Some results on the properties of T -flat, quasi- T -flat, ξ - T -flat,  φ - T -flat, T -semi-symmetric, φ - T - Ricci recurrent and T - φ -recurrent LP-Sasakian manifolds are obtained. It is also proved that an LP-Sasakian manifold satisfying the condition T. S = 0 is an η -Einstein manifold.